Kritik Terhadap Struktur Ilmu Hukum Menurut Paul Scholten - M. Manullang, E. Fernando (Jurnal Hukum & Pembangunan, 2023)
Paul Scholten, a prominent Dutch legal scholar, explains some thoughts in one of his chief article: De Structuur der recthwetenshcap. Essentially it describes some accounts on how legal relations may exist, which he thinks such relations can be both logic and illogical. Scholten even furthermore reiterates such paradigm, the dualism of logic and illogical, also underlies the scientific nature of legal science (jurisprudence). Finally, he also explores on the relations between language and jurisprudence. His all accounts leave some critical notes, as it has some internal contradictions in connection of, as what critical legal theory says, the presence of reifications in legal doctrine.